AR Jersey “make your own jersey” - Seikh Muhamad, Sheikh Alfayeed; Mohd Halmi, Adlan Hariz; Abdul Rahim, Abdul Rahman; Abdul Razak, Nor Irwa Natasha (2021)
AR Jersey Enterprise is the business which produces manufacturing their own customs jerseys. AR stands for the name of the owner, Abdul Rahman. The main reason they started up this business because of they find opportunity in making their own local brand jersey. The owner also found the opportunity in becoming the main centre in providing customs jersey to the community in the area. The business was founded by the owner in 2019. The main activity for this business is jersey printing and selling custom jersey for various types of sports including football, futsal rugby, running and many more with affordable and reasonable price to their customers. Moreover, AR Jersey Enterprise speciality’s is on their customizable printing style. Customer can choose their own design to customize their own jersey. The shop is located at Section 13, Shah Alam and run by the founder and his employees that are function to print or customize the jersey. The business usually produces 30 to 50 products in a day or based on the price of the products is from RM20 to RM60 including the printing services, the price depends on what quality of the jersey. The business main problem is to attract the customer because the people there are still many who do not know about the services provided in this shop because they may think it is just a shop that sells regular jerseys. They are also not exposed to this industry because there have never been other shops that involved in this industry opened in this area.